Association of systemic collagen type IV formation with survival among patients undergoing hemodialysis. - Diana J Leeming (Public Library of Science (PLoS), 2013)
Objective The 7S domain of collagen type IV (P4NP_7S) assessed in plasma represents systemic collagen type IV formation. The objective of the study was to investigate the association of systemic collagen type IV formation with survival among patients undergoing hemodialysis. Methods We performed an observational cohort study of 371 hemodialysis patients. Plasma P4NP_7S was analyzed using a specific enzyme-linked immunosorbent assay detecting the amino-terminal propeptide of type IV procollagen. Association between categories of plasma P4NP_7S concentrations and survival was initially assessed by Kaplan-Meier analysis, then in an adjusted Cox model. Results For hemodialysis patients in the highest category of systemic collagen type IV formation, i.e. plasma P4NP_7S concentrations more than 775 pg/L, an increased risk for death was observed (highest P4NP_7S category vs all other categories, hazard ratio, 1.934; 95% confidence interval, 1.139 to 3.285). Survival analysis showed an increased risk of death in the highest P4NP_7S category compared to the other categories (Chi square 6.903; P = 0.032). Median survival was only 105 days in the highest P4NP_7S category whereas it was 629 days in the medium category, and 905 days in the lowest category. Multivariable-adjusted Cox regression showed increased odds for death with higher age and higher P4NP_7S categories. Systemic collagen type IV formation was associated with plasma concentrations of the collagen IV degradation product C4M (Spearman r = 0.764; P<0.0001) confirming extracellular matrix turnover. Conclusion Among hemodialysis patients elevated systemic collagen type IV formation suggesting accelerating systemic fibrosis was associated with increased risk of death.